OLDER ADULTS’ PERCEPTION OF THE OF THE FACTORS THAT DETERMINE PARTICIPATION TO THE PRE-SPORT VOLIOCHO IN SANTO DOMINGO, HEREDIA, COSTA RICA - Herrera Monge, María Fernanda; Salas Cabrera, Jorge; Fonseca Schmidth, Héctor; Alonso Ubieta, Suyen; Álvarez Bogantes, Carlos (MHSalud: Revista en Ciencias del Movimiento Humano y Salud, 2018)
The objective of this research was to know the factors that determine the participation of the old people in the pre-sport voliocho at the canton of Santo Domingo, Heredia, Costa Rica. This is a grounded theory-based study with a qualitative approach. Twenty older adults participated, aged between 65 and 81 years, practicing pre-sport games for seven years or more. A life story methodology, a semi-structured interview, and the passive observation were used to collect the data. The analysis was carried out by means of the codification in categories established by the Social Cognitive Theory of Bandura (1986). The results show that the main factors of adherence are perceived self-efficacy, expected benefits, self-control, motor skills, social environment relationships, and physical environment. In conclusion, we can appreciate the importance of personal, behavioral, and environmental factors in order to initiate and maintain any physical-sport program in older adults over time.